Renal Preservation Increases Survival Rate in Critically Ill COVID-19 Patients - George, Yohanes; Lolobali, Marilaeta Cindryani (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: COVID-19 infection tends to cause organ dysfunction and disrupts immunity due to cytokine storm. In addition to pulmonary distress and myocarditis due to the aforementioned cytokine storm, another prominent clinical feature of this disease is kidney failure. Maintaining good kidney function, normal creatinine levels, removing cytokine, avoiding fluid overload, and implementing higher level additional measures such as early (renal replacement therapy) are expected to increase survival in critically ill COVID-19 patients. AIM: We aimed to analyze whether renal preservation increases survival rate in critically ill COVID-19 patients METHODS: An observational analytic study was conducted in 53 critically ill COVID-19 patients treated in the ICU (Intensive Care Unit). All patients were treated with either standard therapy with additional renal-focused fluid evacuation and cytokine removal method such as CRRT (continuous RRT) or cytokine removal only with plasmapheresis. RESULTS: investigation through Cox regression analysis revealed that only cumulative balance an creatinine have a significant relationship with mortality (p < 0.05). CONCLUSION: Maintenance of cumulative balance and serum creatinine will increase survival rates.